Source of Lake Vostok Cations Constrained with Strontium Isotopes - Lyons, W. Berry; Welch, Kathleen A.; Priscu, John C.; Tranter, Martyn; Royston-Bishop, George (Frontiers in Earth Science, 2016)
Lake Vostok is the largest sub-glacial lake in Antarctica. The primary source of our current knowledge regarding the geochemistry and biology of the lake comes from the analysis of refrozen lake water associated with ice core drilling. Several sources of dissolved ions and particulate matter to the lake have been proposed, including materials from the melted glacier ice, the weathering of underlying geological materials, hydrothermal activity and underlying, ancient evaporitic deposits. A sample of Lake Vostok Type 1 accretion ice has been analyzed for its 87Sr/86Sr signature as well as its major cation and anion and Sr concentrations. The strontium isotope ratio of 0.71655 and the Ca/Sr ratio in the sample strongly indicate that the major source of the Sr is from aluminosilicate minerals from the continental crust. These data imply that at least a portion of the other cations in the Type 1 ice also are derived from continental crustal materials and not hydrothermal activity, the melted glacier ice, or evaporitic sources.